Rainwater management in urban areas in Poland and Hungary - Piasecki, Adam; Gabriella, Hancz; Kaźmierczak, Bartosz; Górski, Łukasz (Bulletin of Geography. Socio-economic Series, 2023)
The issue of rainwater in urban areas has become more topical due to climate change. In many countries around the world, actions are being taken to minimise the negative consequences of extreme weather phenomena, including short-term, heavy precipitation. The work focuses on the analysis and evaluation of activities related to rainwater management in urban areas in Poland and Hungary. The analysis covers environmental, socio-economic and legal conditions, as well as selected technical solutions related to rainwater management. National- and local-authority measures relating to urban rainwater are discussed and assessed. Legislative solutions in the field of research issues are indicated and compared. The analysis shows differences in approach to elements of rainwater management between the two countries. Attention is given to positive changes in the approaches that national and local authorities and the public take to rainwater. It is indicated that the main barriers to a comprehensive sustainable rainwater management solution in urban areas in Hungary and Poland are financial.